2019
DOI: 10.3390/ijerph16193658
|View full text |Cite
|
Sign up to set email alerts
|

Mental Sleep Activity and Disturbing Dreams in the Lifespan

Abstract: Sleep significantly changes across the lifespan, and several studies underline its crucial role in cognitive functioning. Similarly, mental activity during sleep tends to covary with age. This review aims to analyze the characteristics of dreaming and disturbing dreams at different age brackets. On the one hand, dreams may be considered an expression of brain maturation and cognitive development, showing relations with memory and visuo-spatial abilities. Some investigations reveal that specific electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 223 publications
2
27
0
Order By: Relevance
“…Additionally, the temporo-parietal junction is involved in the cortical network responsible for mental imagery and visual memory [ 41 ]. Interestingly, some studies on DR in children revealed a relationship between dreaming and visuospatial /visual memory skills, which depend on the brain maturation of posterior areas (for a review, see [ 17 , 19 ]). Additionally, studies on the complete cessation of dreaming showed the pivotal role of parietal and occipital areas in generating and recalling the processes of dream experience [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the temporo-parietal junction is involved in the cortical network responsible for mental imagery and visual memory [ 41 ]. Interestingly, some studies on DR in children revealed a relationship between dreaming and visuospatial /visual memory skills, which depend on the brain maturation of posterior areas (for a review, see [ 17 , 19 ]). Additionally, studies on the complete cessation of dreaming showed the pivotal role of parietal and occipital areas in generating and recalling the processes of dream experience [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that dream research is almost totally restricted to young participants, and we know very little about the evolution of these mechanisms during the lifespan (for a review, see [ 17 ]). In particular, the effect of aging on dreaming has been poorly investigated, despite the close relationship between aging and sleep changes [ 18 , 19 ]. It is well known that significant variations characterize the sleep macrostructure in older people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As people age, sleep undergoes some macrostructural and microstructural changes [19][20][21][22]. Concerning macrostructural modifications, the senescence induces shorter sleep duration, longer sleep latency times, a higher number of intra-sleep awakenings, more time spent in the lighter stages of sleep, reduction of Rapid Eye Movement (REM) sleep and deeper stages of Non-Rapid Eye Movement (NREM) sleep, advanced phase (i.e., the anticipation of the sleep beginning and the morning awakening) and increased daytime naps (for a review, see [19]).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, our sample is totally composed of young university students and this could represent a bias that does not allow us to generalize our results. For instance, since the literature on dreaming during lifespan is very poor, 7,8,35 within-subject studies will carry out on larger age ranges (eg, older adults; children). Although the difficulty of obtaining the NREC condition during REM sleep is well known, 1 our sample consisting of 10 subjects with within-subject comparisons is relatively small and further investigation should enlarge the sample size to strengthen the current findings.…”
Section: Dovepressmentioning
confidence: 99%